Anti-corrosion performance of covalent layer-by-layer assembled films via click chemistry reaction on the copper surface. (January 2021) - Zhang, Daquan; Lu, Jiamin; Shi, Cheng; Zhang, Kai; Li, Jin; Gao, Lixin
Graphical abstract: Highlights: Triazole complex films are prepared by covalent layer-by-layer (LbL) assembly. The layer-by-layer (LbL) assembly films provide good anticorrosion performances. The ring-structure with higher binding energy enhances corrosion resistance property. Abstract: Constructing the films with remarkable anti-corrosion performance is the key issue to metal protection. A kind of covalent layer-by-layer (LbL) assembly films of triazole is fabricated on the copper surface in this work. The covalent LbL system provides a promising and efficient protection. The optimum assembly layers are three and the best protection efficiency is 96.9 %. Enhancement in corrosion resistance is due to the formation of the covalent triazole films via the click chemistry reaction catalysed by cuprous oxide. The mechanism of protection is discussed via the surface analysis and the molecular dynamics simulation.